La camera obscura, au-delà du “dispositif foucaldien” proposé par Jonathan Crary dans L’art de l’observateur - Martine Bubb (Appareil)
Techniques of the Observer by Jonathan Crary became a reference text in the field of the studies of the optical devices from the point of view of the espistemology. But the approach very influenced by Michel Foucault of the devices, in particular of the camera obscura, leads the author to privilege the sociology to the detriment of the aesthetics, and can ask question.